Expert System Detecting Symptoms of Game Addiction with The Forward Chaining Method and Certainty Factor - Muhammad Mujib Al Khafid; Sri Sumarlinda; Rina Arum Prastyanti (LPPM Universitas Duta Bangsa Surakarta, 2021)
Games are fun playing activities. In the past, most children and adolescents played games with physical activities, but nowadays children and adolescents play games with their gadgets. Excessive gaming activity can lead to addiction. Game addiction can cause mental illness, even physical illness. This study aims to help gamers as well as the general public to better understand the symptoms of game addiction and early solutions to game addiction. This study uses forward chaining as a plot, namely by collecting symptoms to find the level of addiction and certainty factors as a calculation by calculating the level of trust and distrust of symptoms. In this study, game addiction resulted in 3 levels, low level game addiction, medium level game addiction and high level game addiction.